Periosteal Pecking versus Piston Dry Needling Techniques: A Comparative Study on Pain Reduction in Tennis Elbow - Rahmat Nugraha; Virny Dwiya Lestari; Supartina Hakim; Nur Awalia Syahri Ramdhani; Ikhsan Dermawan Syamsul (Direktorat Politeknik Kesehatan Makassar, 2025)
Lateral epicondylitis is a musculoskeletal disorder caused by overuse of the extensor carpi radialis brevis (ECRB) tendon, characterized by pain and decreased muscle function. This study aimed to compare the effectiveness of piston dry needling and periosteal pecking techniques in reducing pain and improving handgrip strength in patients with lateral epicondylitis. This research employed a quasi-experimental pretest–posttest two-group design involving 20 respondents who were divided into two groups: the piston dry needling group (n = 10) and the periosteal pecking group (n = 10). Both groups received dry needling intervention once per week for four consecutive weeks, for a total of four treatment sessions. The instruments used included the Visual Analog Scale (VAS) to measure pain and a Hand Dynamometer to measure handgrip strength. Data were analyzed using paired t-tests for within-group differences and independent t-tests for between- group comparisons. The results showed that both dry needling techniques were effective in significantly reducing pain and increasing handgrip strength (p<0.001). In the piston dry needling group, the mean VAS decreased from 6.78 ± 0.66 to 2.55 ± 1.27 (Δ 4.23 ± 1.01), and handgrip strength increased from 23.20 ± 3.82 to 28.30 ± 4.12 (Δ 5.10 ± 2.60). In the periosteal pecking group, the mean VAS decreased from 7.25 ± 0.54 to 1.55 ± 0.35 (Δ 5.20 ± 0.70), and handgrip strength increased from 22.60 ± 3.20 to 25.90 ± 3.85 (Δ 3.30 ± 1.60). The independent t-test revealed significant differences in pain reduction (p=0.020) and handgrip improvement (p=0.050). In conclusion Periosteal pecking demonstrated greater effectiveness in reducing pain, while piston dry needling showed a stronger tendency to increase handgrip strength, although the between-group difference for handgrip strength was marginal. Future studies with larger samples or longer follow-up periods are recommended.